Parkin-mediated K63-linked polyubiquitination: A signal for targeting misfolded proteins to the aggresome-autophagy pathway - Olzmann, James A. (2007)
Pathological inclusions containing misfolded proteins are a prominent feature common to many age-related neurodegenerative diseases, including Parkinson’s disease, Alzheimer’s disease, Huntington’s disease, and amyotrophic lateral sclerosis. In cultured cells, when the production of misfolded proteins exceeds the capacity of the chaperone refolding system and the ubiquitin-proteasome degradation pathway, misfolded proteins are actively transported along microtubules to pericentriolar inclusions called aggresomes. The aggresomes sequester potentially toxic misfolded proteins and facilitate their clearance by autophagy. The molecular mechanism(s) that targets misfolded proteins to the aggresome-autophagy pathway is mostly unknown. Our recent work identifies parkin-mediated K63-linked polyubiquitination as a signal that couples misfolded proteins to the dynein motor complex via the adaptor protein histone deacetylase 6 and thereby promotes sequestration of misfolded proteins into aggresomes and subsequent clearance by autophagy. Our findings provide insight into the mechanisms underlying aggresome formation and suggest that parkin and K63-linked polyubiquitination may play a role in the autophagic clearance of misfolded proteins.